Exergy assessment and sustainability of a simple off-shore oscillating water column device. (1st February 2023) - Molina-Salas, A.; Quirós, C.; Gigant, P.; Huertas-Fernández, F.; Clavero, M.; Moñino, A.
Abstract: This paper present a research on the performance efficiency and sustainability of an Oscillating Water Column (OWC) simple off-shore device, accounting for the influence of governing thermodynamic variables (moisture, temperature, pressure) in the compression/expansion polytropic process. The work proposes a simple off-shore OWC experimental set up as the basis of the study. The analysis takes into consideration both gas subsystems inside and outside the OWC, to achieve a better understanding of the conservative nature of entropy system variable, the net exchange balance, the effects on efficiency and exergy destruction, and the interpretation of the OWC as a thermodynamic engine. Results show that, within the context of the set up, moderate wave climate conditions contribute to a better efficiency of the device in terms of output power, providing with a low impact on exergy destruction and high sustainability in terms of renewability index. Highlights: The turbine acts like a restraint of the system. The non-dimensional average pneumatic power output remains essentially constant. The higher the relative depth the lower the relative available useful work obtained. The higher the exergy efficiency, the higher the renewability index. The exergy efficiency and the renewability index are higher in shallow water.